La formación de educadores matemáticos en la Región Brunca - Díaz, Elizabeth (2024)
This investigation presents the main reflections concerning the development of the Bachelor’s and Advanced Degrees of the Mathematics Teaching Programs at the University of Costa Rica’s Southern Region Campus. These programs were offered there first in 2021, and a second generation in 2023. The opening of the programs seeks to solve the need for Mathematics teachers’ training in the Brunca Region which impacts the socio-economic development of the area. The methodology included active observations during the first and second semesters of the 2022 school year, and the first one in 2023, conversations with students and teachers, the program’s annual progress reports and the academic relevance and administrative feasibility studies conducted to inform opening the programs.